Unmasking the Fungal Menace: A Case Report of Chronic Granulomatous Invasive Fungal Sinusitis of Maxilla - Swathi Krishna; Vivekanand Ashok; Shahseena Abdulla; Rosmy John; Prathap Ramalingam (Sinusitis)
Chronic granulomatous invasive fungal sinusitis (CGIFS) is an uncommon type of invasive sinusitis that is characteristically seen in immunocompetent individuals. Common clinical manifestations of this condition include proptosis, cheek swelling, and headache. The pathogenic organism is Aspergillus in the majority of reported cases. Diagnosis is made by histopathological and microbiological examination of tissue specimens. Due to its expansible nature, bone erosion is also associated with this condition. Treatment is surgical clearance/debulking followed by long-term antifungal therapy. Here, we report the case of a 31-year-old male presented with right-side cheek swelling. The patient underwent a medial maxillectomy and was diagnosed with CGIFS. The patient was put on oral voriconazole for 3 months. To conclude, CGIFS is a rare variant of invasive fungal sinusitis that may mimic malignancy or granulomatous diseases such as tuberculosis, rhinoscleroma, and syphilis. Accurate diagnosis is of utmost importance in providing management for CGIFS.